THE IMPACT OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE TOWARDS PLAYER PERFORMANCE THROUGH PLAYER'S WORK SATISFACTION AT BINTANG PRATAMA BASKETBALL CLUB - Iskandar Jurgensen, Stefan Ch.; Singmin Johanes Lo (Dinasti International Journal of Digital Business Management, 2020)
This research purpose way to explored those influence from leadership style towards performance and players' work satisfaction at Bintang Pratama Basketball Club. These research method used quantitative approach. Population and sample were 108 respondents whose members of the club. Data analysis method in this research used Structural Equation Modeling (SEM) with assist of SmartPLS version 3.0 software. The research results indicated that leadership style has a positive and significant impact towards player performance. The leadership style has proven to have a positive and significant influence over the player's work satisfaction. Organizational culture has proven not to have a positive and significant influence towards player performance. Organizational culture has proven to have a positive and significant control across players' work satisfaction. Player's work satisfaction has proven to have a positive and significant control over player performance. Work satisfaction has been shown to mediate the influence of leadership style towards player performance. Work satisfaction has proven to mediate those influence from organizational culture towards player performance.